Pembuatan Aplikasi Game Edukasi “Tebak Nama Pahlawan Nasional” Dengan Construct 2 Berbasis Android (Studi Kasus: MI Islahuddiniyyah) - Ibnu Dhafa Aldiansyach; Farida Nurlaila (CV. Multi Kreasi Media, 2023)
The development of educational software today in Indonesia seems to be increasingly being carried out by educational institutions, either for the benefit of the teaching and learning process or in an effort to increase the efficiency of providing software that contains elements of education. nowadays especially in elementary school Most children feel bored and lazy with learning and feel more like playing than studying. So it is important for children, especially in the world of education. that there are many multimedia learning applications both in the form of applications and educational games that can help foster interest and memory or good grasping power for children. This study discusses the making of learning media in the form of an educational game Guess the Hero's Name with Android-based construct 2. The application of this educational game-based learning media is implemented in the Elementary School of Madrasah Ibtidaiyah Ishlahuddiniyyah, South Tangerang City. Software development using SDLC (Systems Development Life Cycle) Method. Based on the testing of the educational game application Guess the Name of the Hero, it can help introduce Heroes to elementary school students by obtaining a test presentation of 92.16%.